STIMULATING EFFECT OF TRANSCRANIAL ELECTRICAL EXPOSURE ON REPARATIVE PROCESSES IN AN EXPERIMENT - Denis V. Dashko; Maksim A. Uryadnikov (Siberian Journal of Life Sciences and Agriculture)
Electrical stimulation with analgesic current parameters is considered a promising method for developing effective and non-invasive pain relief and therapy methods due to its easily controllable and rapid pain relief, and the absence of side effects, toxic, and allergic complications.